Get different : marketing that can;t be ignored - Michalowicz, Mike (Portfolio, Penguin, 2021)
"From Mike Michalowicz, bestselling author of Profit First, Clockwork, and Fix This Next, a practical and proven guide to standing out in a crowded market. Many business owners are frustrated because they feel invisible in a crowded marketplace. They know they are better than their competitors, but when they focus on that fact, they get little in return. That's because, to customers, better is not actually better. Different is better. And those who market differently, win. In his new marketing book, Mike Michalowicz offers a proven, no-bullsh*t method to position your business, service, or brand to get noticed, attract the best prospects, and convert those opportunities into sales. Told with the same humor and straight-talk that's gained Michalowicz an army of ardent followers, with actionable insights drawn from stories of real life entrepreneurs, this book lays out a simple, doable system based on three critical questions every entrepreneur and business owner must ask about their marketing: 1. Does it differentiate? 2. Does it attract? 3. Does it direct? Different Is Better is a game-changer for everyone who struggles to grow because their brand, message, product or service doesn't stand out and connect with customers--the long-anticipated answer to the defining business challenge of our time"--